BIMBINGAN TEKNIK KURSI KOSONG UNTUK MENINGKATKAN KEBERANIAN MENYAMPAIKAN PENDAPAT MAHASISWA - Khairat Hsb, Fitri Husaibatul (JIEGC Journal of Islamic Education Guidance and Counselling, 2021)
The ability to speak and express opinions in public is one of the competencies that must be possessed by students. This study aims to determine how guidance with the empty chair technique is effective in improving the courage to express opinions in students. The results of the study show that the empty chair technique is proven to be able to help train communication skills and increase confidence in expressing opinions. The theoretical and practical implementation of guidance with the empty chair technique to improve the courage to express opinions in students has a very beneficial value for the development of concepts in guidance and counseling